2017
DOI: 10.1159/000475544
|View full text |Cite
|
Sign up to set email alerts
|

HIV-Associated Cerebellar Dysfunction and Improvement with Aminopyridine Therapy: A Case Report

Abstract: Apart from infectious causes and cerebellar dysfunction associated with acquired immune deficiency syndrome dementia or HIV-associated neurocognitive disorder, cerebellar dysfunction in HIV-positive individuals has been ascribed to granule cell neuronopathy as well as primary cerebellar atrophy without identifiable etiology. We report the case of a patient with progressive cerebellar dysfunction as the primary manifestation of HIV infection. No symptom improvement was seen under combination antiretroviral ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Within dissected brain regions, the observed heterogeneity of morphine-mediated myeloid activation mirrors previous publications that report regional differences in myeloid cell morphology and spatial diversity ( Bachiller et al, 2018 ; Tan et al, 2020 ). Increased CD14+ and CD163+ expression within the frontal lobe and the cerebellum of morphine-dependent animals could hint at more intense inflammation-induced atrophy within these regions ( Hoyer et al, 2017 ; Israel et al, 2019 ). Collectively, this further underscore morphine’s myeloid skewing toward increased neuro-inflammation as further confirmed by our imaging studies that showed elevated myeloid activation based on Iba-1and distorted M1/M2 phenotypes based on CD16, CD163, and CD206 ( Sudduth et al, 2013 ; Hovens et al, 2014 ; Walker and Lue, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Within dissected brain regions, the observed heterogeneity of morphine-mediated myeloid activation mirrors previous publications that report regional differences in myeloid cell morphology and spatial diversity ( Bachiller et al, 2018 ; Tan et al, 2020 ). Increased CD14+ and CD163+ expression within the frontal lobe and the cerebellum of morphine-dependent animals could hint at more intense inflammation-induced atrophy within these regions ( Hoyer et al, 2017 ; Israel et al, 2019 ). Collectively, this further underscore morphine’s myeloid skewing toward increased neuro-inflammation as further confirmed by our imaging studies that showed elevated myeloid activation based on Iba-1and distorted M1/M2 phenotypes based on CD16, CD163, and CD206 ( Sudduth et al, 2013 ; Hovens et al, 2014 ; Walker and Lue, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cerebellar dysfunction in HIV is typically attributed to opportunistic infections such as toxoplasmosis, VZV and CMV, but is also identified in progressive multifocal leukoencephalopathy, autoimmune disease and primary CNS lymphoma. 1,2 There are cases of cerebellar atrophy in the absence of one of these identifiable causes and could be related to the direct neurotoxic effects of the HIV, although CSF viral loads were not documented. [2][3][4][5][6] Our patient had no evidence of opportunistic infections clinically, radiologically or on CSF analysis.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 There are cases of cerebellar atrophy in the absence of one of these identifiable causes and could be related to the direct neurotoxic effects of the HIV, although CSF viral loads were not documented. [2][3][4][5][6] Our patient had no evidence of opportunistic infections clinically, radiologically or on CSF analysis. CSF PCR for JC virus was negative, and although a brain biopsy was not performed to definitively exclude JC-virus associated granule cell neuronopathy, the subsequent rapid clinical recovery was not in keeping with this pathology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The initiation of cART (combinational antiretroviral therapy) drugs ritonavir, darunavir, and lamivudine/zidovudine did not reduce the cerebellar dysfunctions such as ataxia, dementia and neurocognitive disorders associated with HIV infections. The presence of the amino group in the title molecule has the ability to reduce the cerebellar dysfunction [ 18 ]. The physical, biochemical, pharmacological and pharmacokinetic properties of fluorine atom in the title molecules may play an important role in drug design owing to their C—F bond strength, dipole moment, strong electronegetivity and modest lipophilicity [ 19 ].…”
Section: Introductionmentioning
confidence: 99%